A Polymorphism of Insulin-Like Growth Factor Binding Protein 2 Gene Associated with Growth and Body Composition Traits in Kampong Chickens - Furqon, Ahmad; Gunawan, Asep; Ulupi, Niken; Suryati, Tuti; Sumantri, Cece (Jurnal Veteriner; Vol 19 No 2 (2018)DO - 10.19087/jveteriner.2018.19.2.183, 2018)
Insuline-like growth factor binding protein 2 (IGFBP2) is one of the principal binding proteins that has biological functions involved in growth, development, and differentiation. Selection for rapid growth based on molecular Marker Assisted Selection is required to increase production performance. The present study was designed to analyze the associations of IGFBP2 gene polymorphisms with chicken growth and body composition traits. Kampong chicken, a native chicken in Indonesia, is slow-growing chicken. A total of 59 males were used in the current study. Growth and body composition were measured in 24 wk of age. Primers for intron 2 region were designed from genomic chicken sequence. A c.1032C>T SNP of the IGFBP2 gene intron 2 region was detected and PCR-RFLP method was then used to genotype Kampong chicken population. The result showed that IGFBP2 polymorphism was significantly associated with body, carcass, breast, breast muscle, pectoralis minor, leg, and wings weight in Kampong chicken population (P < 0.05). The research suggests that the IGFBP2 gene could be a candidate gene that affects growth and body composition traits in chicken.